ANALYSE STUDENTS' SOCIAL AND PSYCHOLOGICAL VALUES TO BECOME A PROFESSIONAL AUDITOR - Idris, Salma; Junaidi, Junaidi; Anwar, Suhardi M; Sahrir, Sahrir (Universitas Riau, 2024)
This study aims to determine the role of framing, perception, and motivation of accounting students, as well as financial rewards, in influencing their perception of social value and interest in becoming a professional auditor. The collected data involved approximately 864 active students in Indonesia. Structural Equation Modeling (SEM) was utilised to test the research hypotheses. The results indicate that framing, students' perceptions and motivations, and financial recognition regarding a career as an auditor do not significantly affect students' interest in becoming an auditor. However, social value has a significant influence on students' career interest. Additionally, besides psychological factors, future assurance also emerges as a reason for students to choose an auditing career. Thus, stakeholders need to provide encouragement, opportunities, and support to motivate students to consider becoming auditors. The findings of this study contribute to the literature related to career interests in auditing and provide new insights into determining factors that influence students' career choices as future auditors. These research findings can serve as a foundational resource for stakeholders in higher education institutions, particularly accounting departments, to enhance awareness among students about becoming professional auditors, considering that the number of professional auditors in Indonesia is relatively low compared to ASEAN countries.